Peran Budaya Organisasi Terhadap Komitmen Organisasi Ditinjau Dari Persepsi Dosen Universitas Terbuka - Cherly Kemala Ulfa; Ari Juliana; Aulia Keiko Hubbansyah (Universitas Terbuka, 2020)
In the New Normal Era, Universitas Terbuka (UT) emerged as the leading Open Distance Learning Organization. In order to survive and excel, Universitas Terbuka requires a strong organizational commitment from lecturers who are important elements in the learning system at UT. This article aims to examine the influence of organizational culture on organizational commitment for Universitas Terbuka’s lecturers. This was a correlational quantitative research conducted at the UT Headquarters and UT regional offices (UPBJJ UT). The sampling technique used was purposive sampling. Analysis of Simple linier Regression was used to test the hypothesis. The results showed that there was a positive and significant influence of organizational culture on the organizational commitment of UT lecturers. It means the more conducive the organizational culture adapted by the organization is, the higher the level of organizational commitment of UT lecturers have. The implication of this research could be a guide for the management to develop an organizational maintenance program which pays attention to the organizational culture.